Insight to changing morphologic patterns of glomerulopathy in adult Pakistani patients: an institutional perspective. (December 2016) - Hashmi, Atif; Hussain, ZubaidaFida; Edhi, Muhammad; Mumtaz, Shazia; Faridi, Naveen; Khan, Mehmood
Abstract Background Idiopathic nephrotic syndrome encompasses diverse histogenetic patterns and depicts socioeconomic and demographic differences attributable to genetic profile, environmental factors and prevalence of infectious diseases. A lack of renal registry in our country necessitates a need to document changing histologic patterns of nephrotic syndrome as noted in different parts of the world. Methods We retrospectively analyzed 140 patients who underwent renal biopsy at Liaquat National Hospital from January 2009 to December 2013 over a period of 3 years. On the basis of clinical profile cases were segregated into nephritic and nephrotic syndrome and histologic and immunoflourescence findings were analyzed. Results Among 140 cases of glomerulonephritis diagnosed in the study period, 98 cases (70 %) were those of primary glomerulonephritis and 42 were of secondary glomerulopathy (30 %). Membranous glomerulonephritis was the most common primary glomerulonephritis (33.6 %) followed by focal segmental glomerulosclerosis FSGS (20.4 %), whereas lupus nephritis is the most common secondary glomerulopathy (47.6 %) followed by amyloidosis and diabetic glomerulosclerosis (16.6 % each). Conclusion We found a considerable high incidence of membranous glomerulonephritis and FSGS in our population that entails a need to investigate prevalence of associated factors like Hepatitis B and HIV infections in population at risk. Moreover, renal biopsy registry would be instrumental in this regard to record changing disease pattern in this part of the world.